Report Evaluating Safety Culture at UiT - Wolfson, Deanna; Kjellman, Sofia E.; Boomgaren, Marc; Oppvang, Janne; Bjørkeng, Eva Katrin (Septentrio Reports, 2024)
The system of safety associated with lab and fieldwork at UiT The Arctic University of Norway’s Tromsø campus is in serious need of improvement. A volunteer working group of employees evaluated current safety conditions at NT-faculty and beyond, and found a wide range of issues with many overlapping causes. This report contains their findings related to three overarching problem areas: communication, accountability, and training; as well as a range of topical safety areas such as chemicals, fieldwork, and biohazards. The report concludes that significant reform is needed from the top and at all levels to prevent both physical injury and further damage to the working environment.